Digital Event Attendance Application for an Efficient Recording - F Basar, Nurul; A Mohamed, Mohamad; F A Kadir, Mohd; F Abidin, Ahmad; A M Nor, Mustaf (International Journal of Engineering and Technology, 2018)
In universities, there are many events that have been organized to the student. This event helps the student to improve their knowledge and skill. By attending the event, student shows that they are not only academically concerned but also curriculum-oriented. Normally, the event attendance is manually recorded using a piece of paper and a pen. This way, it is not systematically enough and so inefficient. There are many problems arise when using the manual recording. As an alternative to overcome the difficulties, Digital Event Attendance System for Students is developed as an alternative to the manual recording. This proposed system makes use of One-Time Password (OTP) as a security tools during for student registration and Quick Response (QR) code algorithm for students to authenticate and record their attendance. In conclusion, digital event attendance system for student is much more efficient, accurate and systematic than manual recording. This system also will contribute in improving the event attendance system for students because of having the security element and also the good authentication technique.